Effects of Incision, Forced-air Drying, and Pressure Pretreatments on Wet Pockets, Drying Rate, and Drying Defects of Acacia mangium Wood - Elia, Ambrose; Ismail, Jusoh; Alik, Duju; Norsyarina, Welman (NC State University, 2022)
The pretreatment of 7- and 10-year-old Acacia mangium wood using incision, forced-air dying, and pressure were conducted to evaluate the effects on wet pockets, the drying rate, and drying defects. Quarter and rift sawn boards were used in this study. Results showed that the incidence of wet pockets in the incised, forced-air drying, and pressure-treated quarter and rift sawn boards of 7-year-old A. mangium alleviated up to 35% and 79%, 60% and 54%, and 54% and 82%, respectively. In 10-year-old A. mangium, the occurrence of wet pockets was reduced by 68% and 60%, 31% and 73% and 82% and 73% in quarter and rift sawn boards, respectively. Drying rates of 7-year-old A. mangium pressure-treated boards increased by 5% and 40% in quarter and rift sawn boards, respectively. The drying rate was 10% faster for 10-year-old A. mangium pressure-treated boards. The application of the pressure pretreatment yielded no severe drying defects at the end of the drying period, except for a mild collapse in one of the 10-years old A. mangium sample boards. Incision and forced-air drying pretreatments improved the drying rate; however, pressure treatment was found to be superior in reducing wet pockets and drying defects.